2005
DOI: 10.1107/s160053680501901x
|View full text |Cite
|
Sign up to set email alerts
|

3-(2-Ethoxyphenyl)-6-phenyl-1,2,4-triazolo[3,4-b][1,3,4]thiadiazole

Abstract: In the title compound, C17H14N4OS, the central heterocyclic system formed by the five‐membered triazole and thia­diazole rings is planar. The bond lengths within the system indicate some degree of delocalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…For related literature, see: Fornies-Marquina et al (1974); Huang et al (2005); Molina et al (1989); Naveen et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For related literature, see: Fornies-Marquina et al (1974); Huang et al (2005); Molina et al (1989); Naveen et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…(2007). E63, m2297 The molecular structure of 6-methyl-3-phenyl-[1,2,4]triazolo(3,4 -b)-1,3,4-thiadiazole (Fornies-Marquina et al, 1974) and its substituted derivatives (Molina et al, 1989;Huang et al, 2005;Naveen et al, 2006) have been reported, however, no metal complexes of these ligands have so far been reported. In this paper, we report the crystal structure of the title compound, (I), a Cd complex obtained by the reaction of 6-methyl-3-phenyl-[1,2,4]triazolo(3,4 -b)-1,3,4-thiadiazole with cadmium chloride in methanol solution.…”
Section: Sup-1mentioning
confidence: 99%
“…For related literature, see: Fornies-Marquina et al (1974); Huang et al (2005); Naveen et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: APEX2 (Bruker, 2004); cell refinement: SAINT (Bruker, 1999); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 1997); program(s) used to refine structure: SHELXL97 (Sheldrick, 1997); molecular graphics: SHELXTL (Bruker, 1998); software used to prepare material for publication: SHELXTL. The molecular structure of 2-methyl-5-phenyl-s-triazolo(3,4-b)-1,3,4-thiadiazole (Fornies-Marquina et al, 1974) and its substituted derivatives (Huang et al, 2005;Naveen, et al, 2006) have been reported; however, no example of any metal complex of the ligand are known to date. In this paper, we present the crystal structure of the title compound As illustrated in Fig.…”
Section: Data Collectionmentioning
confidence: 99%
“…For related literature, see: Fornies-Marquina et al (1974); Molina et al (1989); Huang et al (2005); Naveen et al (2006).…”
Section: Related Literaturementioning
confidence: 99%